2006
DOI: 10.1080/09513590600585997
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical predictors of endometrial hyperplasiain anovulatory women presenting with amenorrhea

Abstract: The aim of the present study was to determine the prevalence and clinical predictors of endometrial hyperplasia (EH) in amenorrheic women with anovulation. Fifty-seven women were enrolled in the study. Of these, 43 were diagnosed to have polycystic ovary syndrome (PCOS) and 14 to have idiopathic anovulation. All women received transvaginal sonography to assess endometrial thickness (ET), patterns and abnormalities. At the same time, an endometrial biopsy was taken using a Pipelle instrument. The women's age, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
17
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 27 publications
4
17
2
1
Order By: Relevance
“…Our sample of young premenopausal obese patients with PCOS had a 30% rate of endometrial hyperplasia by biopsy, within the reported range of 12%-49% (3)(4)(5). Consistent with others, we noted that simple hyperplasia predominates, but complex and atypical histologies do occur (3)(4)(5).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Our sample of young premenopausal obese patients with PCOS had a 30% rate of endometrial hyperplasia by biopsy, within the reported range of 12%-49% (3)(4)(5). Consistent with others, we noted that simple hyperplasia predominates, but complex and atypical histologies do occur (3)(4)(5).…”
supporting
confidence: 91%
“…Consistent with others, we noted that simple hyperplasia predominates, but complex and atypical histologies do occur (3)(4)(5). Atypia obviously raises the most concern, with 27.5% risk of progression to carcinoma over 20 years (10).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Anthony P et al (2001) and Tingthanatikul Y et al (2006) investigated EH in patients with PCOS in other words they investigated endometrial hyperplasia in risky population. The ET on ultrasound correlates positively with EH.…”
Section: Discussionmentioning
confidence: 99%
“…In view of these findings, an endometrial biopsy should be performed in all women with PCOS (Tingthanatikul et al, 2006). Viola et al, (2008) investigated 12 postmenopausal obese patients and hyperplasia was found 6 of 12 patients (50%) in their study group.…”
Section: Discussionmentioning
confidence: 99%